ANALISIS HUKUM SISTEM PENYELESAIAN SENGKETA ATAS TANAH BERBASIS KEADILAN - HERLINA RATNA SAMBAWA NINGRUM (Jurnal Pembaharuan Hukum, 2014)
Law enforcement bureaucracy in resolving land disputes through litigation and non-litigation often found that in resolving the dispute is considered unjust. Disputes over land and agrarian resources in general seems to be a latent conflict. Of the various cases, rise and sharpening of land disputes not happen instantly, but to grow and develop from seeds that so long it has been deposited. This research method combines doctrinal research and socio-legal research-research, the basis of doctrinal research is research library that includes the primary legal materials, secondary law and tertiary legal materials. The results obtained 1) that the causes of the frequent occurrence of land disputes, among others; System of land administration, land ownership distribution is uneven. The legality of land ownership based solely on the formal proof (certificate), without regard to soil productivity2) Strategy Dispute Settlement System of Land-Based Justice: Strategic Administrative State, Judiciary, Legislative Strategy, Need to establish a separate judiciary in resolving disputes over land